Influence of different corrosive environments on friction and wear characteristics of lubricated wire ropes in a multi-layer winding system. (January 2022) - Chang, Xiang-dong; Peng, Yu-xing; Cheng, De-qiang; Zhu, Zhen-cai; Wang, Da-gang; Lu, Hao; Tang, Wei; Chen, Guo-an
Graphical abstract: Highlights: The COF of lubricated wire ropes fluctuates between approximately 0.15 and 0.28. It is mainly adhesive wear of wire rope under different lubrication conditions. Corrosive solutions degrade the protective properties of lubricating grease/oil. Dilute sulfuric acid solution is the most harmful to lubricated wire ropes. Corrosive environment can degrade the performance of a lubricant before it fails. Abstract: Corrosion, friction and wear of wire ropes always exist in multi-layer winding systems. They lead to the lubrication failure and service performance degradation of wire rope. To reveal the tribological properties of wire rope in service, the coefficient of friction (COF), friction temperature rise and surface wear characteristics of wire rope with different lubrication and corrosion conditions were investigated. The experimental results show that friction parameters of the lubricated wire ropes are relatively small, which are obviously affected by the sliding stroke and velocity. The COF fluctuates between approximately 0.15 and 0.28, and the friction temperature rise is reduced to below 7 °C. Additionally, the corrosion solutions degenerate the anti-friction and anti-wear properties of the lubricating grease and oil. The COF and friction temperature rise of the oil lubricated wire rope increase greatly when the rope sample is corroded by sea-water and dilute sulfuric acid solution. The sliding wear mechanism and lubrication stage of the lubricated wire ropes is adhesive wear and boundary lubrication, respectively. Furthermore, dilute sulfuric acid solution is the most harmful to the friction-reduction and wear-resistance of the lubricating grease and oil used for wire rope, followed by sea-water solution and fresh water solution.